2009
DOI: 10.1016/j.jsv.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Power flow analysis for a floating sandwich raft isolation system using a higher-order theory

Abstract: A higher-order sandwich theory is implemented in conjunction with an equivalent mobility-based power flow progressive method to determine power flow for a sandwich configured floating raft vibration isolation system. The power spectrum changes in whole frequency range effectively when core materials' properties change. It is also shown that the loss factors of the sandwich configured floating raft influence the power flow transmitted to the foundation effectively in the medium-to high-frequency range and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Research objects have been developed from rigid models [15,16] to flexible ones [17][18][19], and the performance index has been developed from force or velocity indices [20][21][22] to power flow indices [17,18,23]. Du [24] found that the force transmissibility increased 20∼30 dB, and the noise radiated by the foundation increased about 22 dB when wave effects of isolators are considered.…”
Section: Introductionmentioning
confidence: 99%
“…Research objects have been developed from rigid models [15,16] to flexible ones [17][18][19], and the performance index has been developed from force or velocity indices [20][21][22] to power flow indices [17,18,23]. Du [24] found that the force transmissibility increased 20∼30 dB, and the noise radiated by the foundation increased about 22 dB when wave effects of isolators are considered.…”
Section: Introductionmentioning
confidence: 99%
“…Much of research results about vibration power flow problem were carried out. Choi et al 10 applied higher order sandwich theory in conjunction with an equivalent mobility-based power flow progressive method to determine power flow for a sandwich-configured floating raft vibration isolation system. For the submerged cylindrical shells, the wave propagation approach was often used to study the vibro-acoustic problem.…”
Section: Introductionmentioning
confidence: 99%
“…She found that the in-plane motions had significant effects on the power flow in median and high frequencies. Choi et al [29] presented a higherorder sandwich theory in conjunction with an equivalent mobility-based power flow progressive approach to determine power flow for a sandwich configured floating raft vibration isolation system.…”
Section: Introductionmentioning
confidence: 99%
“…As the error is inevitable in practical applications, to study the effects of the error of control force on the control results becomes necessary. Moreover, the active power flow in the beams and plates is much studied [21][22][23][24][25][26][27][28][29][30][31][32][33], with few reports on the reactive power flow in finite structures.…”
Section: Introductionmentioning
confidence: 99%